THE INFLUENCE OF ORGANIZATIONAL COMMUNICATION AND COMPENSATION AND BENEFITS ON JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT THROUGH WORK STRESS AS A MODERATING VARIABLE (A CASE STUDY OF MADURESE GROCERY STORES IN MALANG) - Muhammad Maulana Ibrahim; Arief Noviarakhman Zagladi (CV. Radja Publika, 2026)
This study aims to analyze the influence of organizational communication and compensation and benefits on job satisfaction and organizational commitment, with work stress as a moderating variable in Madurese grocery stores in Malang. A quantitative approach with an explanatory research design was employed, using a survey method through questionnaires distributed to 100 respondents selected by purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that organizational communication and compensation and benefits have a positive and significant effect on job satisfaction and organizational commitment. Conversely, work stress has a negative and significant effect on both job satisfaction and organizational commitment. Furthermore, work stress significantly moderates the relationship between organizational communication and compensation with job satisfaction and organizational commitment by weakening these relationships. These findings highlight the importance of effective communication, fair compensation systems, and proper stress management in enhancing employee satisfaction and commitment, particularly in MSMEs. This study provides both theoretical contributions to human resource management literature and practical implications for improving organizational performance in small business contexts.